Emerging processing technologies for improved digestibility of muscle proteins. (April 2021) - Bhat, Zuhaib F.; Morton, James D.; Bekhit, Alaa El-Din A.; Kumar, Sunil; Bhat, Hina F.
Abstract: Background: The ever-expanding human population demands some novel ideas and ingenious ways to produce foods of sufficient quality and quantity that would meet the protein requirements of humans. Muscle proteins, both lab- and farm-grown, are going to contribute their part and play an important role in near and distant future. However, finite animal and land resources and increasing environmental concerns will limit our capacity to produce adequate muscle proteins for all. A viable option to sustain protein resources is to reduce the food wastage and to fully utilize existing muscle proteins by improving the digestibility of muscle foods. The use of novel food processing techniques may support such objectives. However, this is relatively nascent area and there is an urgent need to expand our understanding by examining the basic knowledge of how muscle proteins processed under different conditions behave in the gastrointestinal environment, both in vivo and in vitro . Scope and approach: The present review highlights some of the novel processing techniques of improving muscle protein digestibility and discusses how different processing conditions affect the digestibility of muscle proteins under gastrointestinal digestion environments. The underlying mechanisms have been discussed in detail and supported by the current literature. Key findings and conclusions: Protein digestibility of muscle foods can be improved by employing several thermal and non-thermal emerging technologies, which have potential to improve the susceptibility of muscle proteins to gastrointestinal proteases. By affecting the structural (quaternary, tertiary or even secondary) and functional properties of the proteins and muscle microstructure, emerging technologies such as pulsed electric field, high-pressure, ultrasound and hydrodynamic shockwave, can induce denaturation and affect the unfolding and refolding of the proteins, thereby affecting both the diffusion of gastrointestinal proteases deep into the protein matrix as well as their accessibility to cleavage sites. The denaturation patterns of the processed proteins are not always predictable and depends on the processing conditions and the origin of the protein, thereby affecting protein digestibility positively or negatively. Extensive research is required to understand optimum processing conditions of these emerging technologies towards the favourable effects on the protein digestibility as affected by protein structure and muscle configuration to enable processing conditions suitable for different meat cuts and from different species. There is a need to improve and standardise the methods used to study meat digestion particularly ' in vitro' . Highlights: Novel technologies have potential to improve digestibility of muscle proteins. Pulsed electric field, high-pressure, ultrasound and shockwaves affect digestibility of muscle proteins. Underlying mechanisms involve alterations in protein structure and muscle microstructure. Processing conditions determine the overall effect on digestibility. These technologies can help in designing muscle foods with superior digestibility.